UTILIZING QUIPPER SCHOOL FOR IMPROVING READING COMPREHENSION OF RECOUNT TEXT - Siti Mariam; Catur Kepirianto; Ma’rifatul Fadlilah; Nafisah Mardhiana (University of Kuningan, 2022)
This study aims at explaining the implementation of using Quipper School for improving reading comprehension of recount text and also describing the students’ engagement in the use of this digital media. This research design employed qualitative descriptive. The data collection technique used interview and documentation. To analyze the data, the researchers used data reduction, data mapping, inference, or validation. The participants of this study were the eleventh grade students and the English teacher at a public high school in Semarang, Indonesia. The research shows that students and the teacher have been helped in the teaching and learning process using Quipper School application. Students can learn reading materials with this digital medium during online learning due to the Covid19 pandemic. Students also enjoy discussion and interest in educational materials that are easy to implement and have easy access to the digital media. There were also interactive conversations about student learning issues to help students understand the reading content materials more easily. Keywords: digital media; learning; Quipper school; reading; recount text